Modelling and self-tuning pressure control in an injection molding cavity - Varela Villalobos, Alfredo (Rev. Téc. Fac. Ing. Univ. Zulia)
Injection molding of thermoplastics is a cyclical process where a granular polymer is melted and injected into the cavity, molded under pressure and ejected after solidification. The control of cavity pressure profile from cycle to cycle during the filling stage is important to ensure quality injection molded parts. First, open-loop experiments are performed to determine and verify an appropriate model order. Secondly, due to the time-varying characteristics of this process, a self-tuning algorithm with an observer is employed for controlling the cavity pressure time profile to a set-point trajectory. The model parameters are determined on-line using the recursive least-squares estimation algorithm, and the controller parameters are calculated using the pole location procedure. In order to reduce the controller saturation, the self-tuning algorithm is implemented along with a first-order observer and state feedback.